2020
DOI: 10.1101/2020.11.14.20231712
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Facilitated transition in HIV drug trial closure: a conceptual model for HIV post-trial care

Abstract: Within the HIV clinical trial field, there are gaps in existing ethical regulations in relation to post-trial care. There is need to develop post-trial care guidelines that are flexible and sensitive to local contexts and to the specific needs of different groups of participants, particularly in low income contexts. Evidence regarding HIV trial closure and post-trial care is required to underpin the development of appropriate policies in this area. This article reports research from Uganda that develops a new … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…In addition to these, research staff in this study have recommended the need for: more person-centred post-trial care taking into account the psychological needs of participants; a more active researcher-led linkage to care approach; researcher (and other stakeholder) engagement with trial participants following trial exit; and a more person-centred approach to the provision of trial feedback. The proposed approach is further detailed in the Model of Facilitated Transition in HIV Drug Trial Closure (Nalubega et al, 2021) and is recommended for HIV trial closure practice in Uganda and related settings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to these, research staff in this study have recommended the need for: more person-centred post-trial care taking into account the psychological needs of participants; a more active researcher-led linkage to care approach; researcher (and other stakeholder) engagement with trial participants following trial exit; and a more person-centred approach to the provision of trial feedback. The proposed approach is further detailed in the Model of Facilitated Transition in HIV Drug Trial Closure (Nalubega et al, 2021) and is recommended for HIV trial closure practice in Uganda and related settings.…”
Section: Discussionmentioning
confidence: 99%
“…The study adopted a qualitative, constructive grounded theory approach (Charmaz, 2014), which resulted in construction of a model of 'Facilitated Transition' to guide post-trial practice -reported in another paper (Nalubega et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation